Association Between C‐Reactive Protein and Atrial Fibrillation Recurrence After Catheter Ablation: A Meta‐analysis. Issue 9 (10th June 2013) - Jiang, Zhouqin; Dai, Limeng; Song, Zhiyuan; Li, Huakang; Shu, Maoqin
Abstract Background Atrial fibrillation (AF) is associated with inflammation. Increased serum C‐reactive protein (CRP) levels are important representatives of an inflammatory state of AF. A variety of studies have evaluated whether increased CRP levels have an association with AF recurrence after catheter ablation. However, the results remain inconsistent, therefore, this meta‐analysis was conducted to offer suggestions. Hypothesis Increased baseline CRP have an association with AF recurrence after catheter ablation. Methods Electronic databases including PubMed, Embase, Medline, ISI Web of Knowledge, and ScienceDirect were searched until December 31, 2012 for any CRP‐associated studies. Overall and subgroup analyses were performed. Standardized mean difference (SMD) and 95% confidence interval (CI) were used to evaluate the associations between CRP levels and postablation AF recurrence. Statistical analysis was performed with Review Manager 5.2 and Stata 11.0. Results Seven available studies were identified, which included 526 patients (179 recurrence vs 347 no recurrence). Overall, increased baseline CRP levels had significant positive association with postablation AF recurrence. The SMD in the CRP levels was 0.65 units (95% CI: 0.30‐0.99), and the z‐score for overall effect was 3.70 (P = 0.0002). The heterogeneity test showed that there were moderate differences between individual studies (P = 0.006, I2 = 67%). Metaregression revealed that different sample sizes of studies possibly accounted for the heterogeneity. Positive associations were also found in subgroup analyses based on sample size. When stratifying for ethnicity, similarly significant associations were found in both European (Caucasian) and Asian populations. Conclusions Investigations demonstrate that baseline CRP levels are greater in patients with postablation AF recurrence. Further studies with larger sample size and delicate design for CRP should be conducted.